Repairing the Brain by SCF+G-CSF Treatment at 6 Months Postexperimental Stroke: Mechanistic Determination of the Causal Link Between Neurovascular Regeneration and Motor Functional Recovery. (June 2016) - Cui, Lili; Wang, Dandan; McGillis, Sandra; Kyle, Michele; Zhao, Li-Ru
Stroke, a leading cause of adult disability in the world, is a severe medical condition with limited treatment. Physical therapy, the only treatment available for stroke rehabilitation, appears to be effective within 6 months post-stroke. Here, we have mechanistically determined the efficacy of combined two hematopoietic growth factors, stem cell factor (SCF) and granulocyte-colony stimulating factor (G-CSF; SCF + G-CSF), in brain repair 6 months after cortical infarct induction in the transgenic mice carrying yellow fluorescent protein in Layer V pyramidal neurons (Thy1-YFP-H). Using a combination of live brain imaging, whole brain imaging, molecular manipulation, synaptic and vascular assessments, and motor function examination, we found that SCF + G-CSF promoted mushroom spine formation, enlarged postsynaptic membrane size, and increased postsynaptic density-95 accumulation and blood vessel density in the peri-infarct cavity cortex; and that SCF + G-CSF treatment improved motor functional recovery. The SCF + G-CSF-enhanced motor functional recovery was dependent on the synaptic and vascular regeneration in the peri-infarct cavity cortex. These data suggest that a stroke-damaged brain is repairable by SCF + G-CSF even 6 months after the lesion occurs. This study provides novel insights into the development of new restorative strategies for stroke recovery.